Luther's treatise On Christian freedom and its legacy - Kolb, Robert 1941- (Lexington Books/Fortress Academic, 2020)
"This book analyzes Luther's treatise On Christian Freedom and its revolutionary re-definition of what it means to be Christian as one freed by Christ from sin, the accusation of God's law, and death in order to be bound or bonded to the neighbor. Placing the treatise in its historical context, Robert Kolb examines its impact to the present day"--
Keywords: Luther, Martin -- 1483-1546 -- Von der Freiheit eines Christenmenschen; Geschichte; Rezeption; Luther, Martin / 1483-1546 / Tractatus de libertate Christiana; Liberty / Religious aspects / Christianity; Tractatus de libertate Christiana (Luther, Martin)